Karcinom pankreatu - současný efektivní diagnosticko-terapeutický postup - Ryska, Miroslav (Casopis lekaru ceskych, 2016)
UNLABELLED: Pancreatic cancer is solid malignant, chemoresistant tumour with unfavourable prognosis. Radical resection with adjuvant chemotherapy is only potential curable therapeutic modality enabling to prolong survival of 20 % patients. Borderline conception contents active approach to primary non-resectable patients to reach resectability by neoadjuvant chemo(radio)therapy. Palliative and symptomatic therapy is indicated in about 70 % patients.In the case of suspicious of pancreatic cancer, patient should be referral to specialized centre. Effective diagnostic therapeutic approach only guarantees optimal quality of life of these patients. KEY WORDS: pancreatic cancer - diagnosis and therapy, multidisciplinary approach, quality of life.
Keywords: Neoadjuvant Therapy; Neoplasm Staging; Pancreatectomy; Combined Modality Therapy; staging nádorů; prognóza; nádory slinivky břišní; protinádorové látky; Humans; Quality of Life; pankreatektomie; Antineoplastic Agents; Pancreatic Neoplasms; kvalita života; kombinovaná terapie; Prognosis; lidé; neoadjuvantní terapie